2020
DOI: 10.3390/jdb8030012
|View full text |Cite
|
Sign up to set email alerts
|

A Synthetic Peptide, CK2.3, Inhibits RANKL-Induced Osteoclastogenesis through BMPRIa and ERK Signaling Pathway

Abstract: The skeletal system plays an important role in the development and maturation process. Through the bone remodeling process, 10% of the skeletal system is renewed every year. Osteoblasts and osteoclasts are two major bone cells that are involved in the development of the skeletal system, and their activity is kept in balance. An imbalance between their activities can lead to diseases such as osteoporosis that are characterized by significant bone loss due to the overactivity of bone-resorbing osteoclast… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 104 publications
1
15
0
Order By: Relevance
“…Osteoclastogenesis and the activity of osteoclasts are reliant on osteoblasts [ 16 , 27 , 28 , 29 , 30 ]. Osteoblasts secrete two proteins that are necessary for osteoclast function and differentiation: macrophage colony stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-β ligand (RANKL) [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Osteoclastogenesis and the activity of osteoclasts are reliant on osteoblasts [ 16 , 27 , 28 , 29 , 30 ]. Osteoblasts secrete two proteins that are necessary for osteoclast function and differentiation: macrophage colony stimulating factor (M-CSF) and receptor activator of nuclear factor kappa-β ligand (RANKL) [ 31 , 32 , 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…The M-CSF and RANKL signaling pathways promote cell differentiation, survival, and proliferation by activating the Akt, Erk, NF-κB, and MAPK pathways [ 18 ]. It has previously been reported that murine RAW264.7 cells of the monocyte/macrophage lineage respond to these factors and can be used as a model for studying osteoclastogenesis [ 16 , 27 ]. However, the effects of M-CSF and RANKL in bone marrow cells isolated directly from human femoral heads remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…The difference in RANK signaling is that Tumor Necrosis Factor Receptor-associated Factor Protein 6 (TRAF6) rather than XIAP recruits TAB1/TAB2 to the RANK receptor, activating TAK1. MAPK signaling converges to increase the expression and translocation of NFATc1a, an essential transcription factor that leads to the upregulation of osteoclast genes for fusion and activation [ 69 , 73 , 137 , 138 , 139 , 140 ] This overlap in MAPK signaling between the RANKL pathway and the BMP pathway may contribute to the enhancement of osteoclastogenesis ( Figure 5 ).…”
Section: Bmp-signaling Pathway In Osteoclastsmentioning
confidence: 99%
“…Nevertheless, the dual impact on bone formation and bone resorption makes the BMP pathway a potential therapeutic target for osteoporosis. The peptide CK2.3 utilizes the BMP pathway in the absence of a BMP ligand to stimulate osteoblast mineralization and inhibit osteoclast resorption [ 140 , 189 , 190 , 191 , 192 ]. Furthermore, CK2.3 increases mineralization in osteoporotic patients where BMP2 is not [ 167 ].…”
Section: Treatments For Osteoporosismentioning
confidence: 99%
“…In the first article [ 1 ], Nguyen and colleagues investigated bone remodeling and cell signaling between the following two types of bone cells: osteoblasts and osteoclasts. They report that a peptide inhibitor of osteoclast development promotes bone formation by activating ERK and promoting the expression of BMPR1a.…”
mentioning
confidence: 99%